Gestational Thrombocytopenia Complicated with Macrosomia, Failure to Progress in Active Labor, and Postpartum Hemorrhage - Shih-Peng Mao; Cheng-Chang Chang; Shu-Ying Chen; Hung-Chung Lai (Taiwanese Journal of Obstetrics & Gynecology, 2007)
Objective: Gestational thrombocytopenia is a rare event, and the etiology is unknown. Generally, there is no need for intervention because of the absence of coagulopathy. However, when complicated with other obstetric conditions, care should be taken to prevent a dangerous cascade. Here, we present a patient with severe gestational thrombocytopenia complicated with macrosomia, failure to progress in active labor, and severe postpartum hemorrhage after cesarean section. Case Report: A 25-year-old, gravida 4, para 0, patient from our antenatal clinic developed thrombocytopenia with advancing gestation. Severe thrombocytopenia (platelets, 53 × 109/L) and suspected macrosomia were noted at 39 3/7 weeks of gestation. Induction of labor was conducted for a planned vaginal delivery, but the active labor failed to progress. A cesarean section was performed instead, resulting in immediate postpartum hemorrhage due to uterine atony. Uterine massage, direct compression, and 10 IU of oxytocin (Piton-S, 10 IU/mL; PT Organon, Indonesia) improved uterine contraction only temporarily. Misoprostol was administered rectally. The patient was given a transfusion of packed red blood cells and single-donor platelets. Her condition stabilized after intensive intervention. Conclusion: Gestational thrombocytopenia does not usually require treatment if there is no bleeding tendency. However, when other bleeding complications are present, it may exacerbate coagulopathy and exhaust the platelet reserve, thereby worsening the condition. If surgical intervention cannot be avoided, blood and platelet transfusion before a cesarean delivery is highly recommended in severe gestational thrombocytopenia.